2017
DOI: 10.18632/oncotarget.16012
|View full text |Cite
|
Sign up to set email alerts
|

Nitrobenzylthioinosine mimics adenosine to attenuate the epileptiform discharge of hippocampal neurons from epileptic rats

Abstract: Nitrobenzylthioinosine (NBTI), a specific inhibitor of type 1 equilibrative nucleoside transporter, could regulate the extracellular adenosine concentration and have protective roles in seizures. However, the protection mechanism of NBTI in seizures remains poorly understood. Here, the expression pattern and subcellular distribution of adenosine A1 receptor were detected by Western blot analysis and double-labeling immunofluorescence staining in Lithium Chloride-Pilocarpine induced epileptic rat model. At 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
4
0
1
Order By: Relevance
“…and hippocampal injections of nBTi, a selective enT1 inhibitor, decreased the number of seizures and prolonged the latency of the first seizure in rats, indicating that enT1 plays an important role in the development of epilepsy (29). Therefore, enT1 may be a novel therapeutic target for the control of epileptic seizures in the clinic (22,28). Based on the results of western blot analysis in the present study, enT1 expression levels 3 days after seizure induction were significantly lower in the SB203580 group than in the epilepsy group, showing that inhibition of the p38 MaPK signaling pathway modified ENT1 expression levels in epileptic rats.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…and hippocampal injections of nBTi, a selective enT1 inhibitor, decreased the number of seizures and prolonged the latency of the first seizure in rats, indicating that enT1 plays an important role in the development of epilepsy (29). Therefore, enT1 may be a novel therapeutic target for the control of epileptic seizures in the clinic (22,28). Based on the results of western blot analysis in the present study, enT1 expression levels 3 days after seizure induction were significantly lower in the SB203580 group than in the epilepsy group, showing that inhibition of the p38 MaPK signaling pathway modified ENT1 expression levels in epileptic rats.…”
Section: Discussionsupporting
confidence: 51%
“…Our previous study (20) confirmed that the specific p38 MaPK inhibitor SB203580 alleviated epileptic seizures in Se rats. nitrobenzothioinosine (nBTi), a selective inhibitor of enT1 (21), blocks the transport of adenosine into cells and increases extracellular adenosine levels, thus exhibiting a protective effect against epileptic seizures (22). a number of studies have revealed that a1r, a member of the adenosine system, has significant anticonvulsant effects (13,23).…”
Section: Inhibition Of P38 Mapk Regulates Epileptic Severity By Decreasing Expression Levels Of A1r and Ent1mentioning
confidence: 99%
“…In several epilepsy models, adenosine has been shown to exert an anticonvulsant effect (Boison, 2012;Masino et al, 2014), which appears to be mainly mediated by A1R (Li et al, 2007). ENT1 may be considered a therapeutic target for the control of epileptic seizures (Huang et al, 2017). Indeed, intraperitoneal and hippocampal injections of nitrobenzythioinosine (NBTI), a specific inhibitor of ENT1, decreased the number of seizures in rats (Xu et al, 2015), while blood brain barrier permeable ENT1 inhibitors have shown anti-epileptic effects in different mouse models (Ho et al, 2020).…”
Section: Equilibrative Transportersmentioning
confidence: 99%
“…Immunofluorescence was performed as previously described by our laboratory 19 . Briefly, brain tissue sections were fixed in 4% polyformaldehyde for 1 min.…”
Section: Methodsmentioning
confidence: 99%